PENGARUH RASIO LIKUIDITAS TERHADAP RETURN ON EQUITY PADA BANK UMUM SYARIAH DI INDONESIA - Rizka Mauliza; Sufi Sufi (Program Studi Administrasi Bisnis, 2021)
Maximizing asset management and limiting risks, such as liquidity risk, are two ways to achieve maximum profitability (ROE) (Cash Ratio, Non Performing Loan and Loan to Deposit Ratio). The goal of this study was to look into and assess the impact of the Cash Ratio (CR), Non-Performing Loans (NPL), and Loan to Deposit Ratio (LDR) on Return on Equity (ROE) in Indonesian Islamic banks. This study employs quantitative approaches, with secondary data in the form of time series data produced between 2015 and 2019. Multiple linear regression analysis was used to analyze the data in this study. The results demonstrate that the Cash Ratio has a positive sign and has a value of tcount > ttable (2,512>1,69726), indicating that the Cash Ratio has a considerable positive effect on Return on Equity at Indonesian Islamic Commercial Banks. Non-Performing Loan (NPL) has a negative sign and has a value of tcount> ttable (2,289> 1,69726), indicating that it has a considerable negative impact on Islamic Commercial Banks' Return on Equity in Indonesia. With a large effect of 2.02 percent, the Cash Ratio, NPL, and LDR have a pretty strong impact on the Return on Equity (Y) of Islamic Commercial Banks in Indonesia. The findings of this study provide information for bank management to monitor more frequently and take the appropriate actions to anticipate liquidity problems and maintain financial balance in Indonesian Islamic commercial banks.